2019
DOI: 10.3390/su11154171
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Airport Servicescape on Airport Users’ Behavioral Intentions: A Case Study of Incheon International Airport Terminal 2 (T2)

Abstract: The purpose of this study is to analyze the effects of physical and social servicescapes on cognitive and affective satisfaction, as well as airport image, with gender as a moderating effect between variables. A total of 283 airport users were surveyed, and structural equation modeling was used to investigate the relationships between variables. The results showed that only physical servicescape had a significant effect on cognitive and affective satisfaction, and affective satisfaction had a significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Finally, the present study broadens existing literature on the situational effects of the servicescape-driven responses by considering the gender difference in the theoretical framework. Although gender as a moderator has been extensively addressed in tourism and hospitality, limited research examines servicescape-related gender effects (Park and Ryu, 2019). This study enriches the servicescape literature by examining the gender difference regarding the effects of servicescape elements on customer engagement and CCBs, which provides a clear understanding on the gender differences in responses to environmental elements of hotels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Finally, the present study broadens existing literature on the situational effects of the servicescape-driven responses by considering the gender difference in the theoretical framework. Although gender as a moderator has been extensively addressed in tourism and hospitality, limited research examines servicescape-related gender effects (Park and Ryu, 2019). This study enriches the servicescape literature by examining the gender difference regarding the effects of servicescape elements on customer engagement and CCBs, which provides a clear understanding on the gender differences in responses to environmental elements of hotels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Airport impacts studies Economic (Appold, 2015) (Augustyniak, 2009) (Butler & Kiernan, 1986) (Basso, 2007) (Diaz Olariaga & Ávila Álvarez, 2015 (Fasone, Giuffrè & Maggiore, 2012) (Forsyth, 2006) (Gutiérrez et al, 1999) (Hanlon, 1995) (Dimitriou, 2018) (Kuper, Massacci, Shim & Williams, 2020) (Li andLoo, 2016) (Mense &Kholodilin, 2014) (Morimoto, 2019) (Pitfield, 1981) (Takebayashi, 2011) (Tosun, 2002) (Qin & Tian, 2019) Environmental (Chaouk, Pagliari & Moxon, 2020 (Gratton, Padhra, Rapsomanikis & Williams, 2020) (J. Torija, 2018) (Maeda, 1991) (Mense & Kholodilin, 2014) (Ren, Cao & Liu, 2018) (Sahrir, Bachok & Osman, 2014) (Zheng, Peng & Hu, 2020) Social (Akehurst, 1999) (Alpes, 2015) (Bogicevic, Bujisic, Bilgihan, Yang & Cobanoglu, 2017) (Halpern, 2012) (Rowe & Pitfield, 2018) (Pabedinskaitė & Akstinaitė, 2014) (Park & Ryu, 2019) (Sahrir, Bachok & Osman, 2014) (Tezel et al, 2019) (Wilke, Majumdar & Ochieng, 2015) Tourism (Doerr, Dorn, Gaebler & Potrafke, 2020)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As seen in KAC's implementation of biometric e-gate technology, high expectations were not matched. A lack of active use by passengers in the airport showed a resistance to the use of this innovative technology [1]. This indicated that it is not easy to adopt to an innovation despite numerous benefits, such as the elimination of bringing an ID card and reduced waiting time [26].…”
Section: Underlying Theory: Resistance To Innovationmentioning
confidence: 99%
“…Global leading airports, such as Incheon International Airport (IIA), are looking to provide improved passenger services in order to maintain the overall airport experience. This has been cited as one of the key factors for developing sustainable airport operations and their own competitiveness [1]. Therefore, passenger service quality within airports are evaluated every year.…”
Section: Introductionmentioning
confidence: 99%